Optimalisasi Asesmen Sekolah dalam Membangun Peradaban Sekolah Berbasis Kepemimpinan dan Layanan Pendidikan Berkualitas - Sandi Budiana; Nurlinda Safitri; Roy Efendi; Rendra Gunawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Quality education requires collaboration among various stakeholders, teacher professionalism, and transformative leadership. However, in reality, teachers still face challenges related to professionalism in developing teaching modules, as well as supervision that is merely an administrative formality. This community service activity aims to optimize educators’ understanding of assessment and revitalize the role of school leadership in the Rangkasbitung area. The implementation method employed an educational approach, featuring strategic content delivery and interactive dialogue with 24 representatives from high schools and vocational schools in the Rangkasbitung area. The results of the community service initiative indicate significant changes among the participants, as they have begun to recognize the importance of various competencies, including digital literacy and meaningful assessment. Additionally, school leaders have committed to shifting their mindset regarding supervision toward more effective mentoring.